Neuromuscular fatigue and explosive strength in the legs. New approach to physical preparation in tennis - Osete, A.; Mechón, I.; Gil Herrera, J.; Cabaleiro, F.; González, D.; Squillari, F. (Coaching and Sport Science Review, 2025)
Despite the numerous existing studies, neuromuscular fatigue continues to be an inexhaustible topic in the study of sports training. The article addresses the study of explosive power in legs in tennis training for high competition. While most of the existing literature points to the decrease in endurance performance and coordination motor skills after a strenuous match, our study, carried out on a sample of 204 athletes between 12 and 18 years old within the framework of competitions organized by the Argentine Tennis Association, demonstrates how the explosive power of the legs increases after a long-lasting match. Considering that the sporting fact is multifactorial and that the physiological, neurological and psychological factors that must be considered to enhance training, two conclusions emerge from the study: the value of the finding to reevaluate tennis training and the importance of research in real competition situations.